Persepsi mahasiswa terhadap praktik profesi ners pada masa pandemi covid-19 - Fitri Dian Kurniati; RR Viantika Kusumasari; Muskhab Eko Riyadi (Health Sciences and Pharmacy Journal, 2022)
The impact of the COVID-19 pandemic on the education sector has changed the learning process, which was originally mostly done conventionally, into online learning. Likewise at the stage of nursing professional education. The learning structure of the nursing profession study program is based on clinical practice. However, this cannot be fulfilled due to the COVID-19 pandemic. The purpose of this study is to determine students' perceptions on the nursing professional practice  in Stikes Surya Global Yogyakarta during the covid-19 pandemic. This type of research was qualitative study. Participants were selected by purposive sampling with the inclusion criteria of nursing professional education study program students exposed to offline and online learning, registered in the second semester of the 2020/2021 academic year. Data were collected by means of in-depth interviews. Data analysis was carried out using content analysis. The results showed that students' perceptions were divided into two categories, namely inhibitors and supporters. The inhibiting sub-categories consist of the ineffectiveness of the online learning process, costs, and internet networks. Supporting sub categories consist of studying UKNI questions and updating technology developments. Offline learning was categorized into two, namely inhibiting and supporting. The inhibiting sub-category consists of a lack of facilities and more expenses from students. The supporting sub-categories consist of readiness for field practice, the use of complete PPE, and permission from parents. The conclusion of this study was that the perception of nursing profession students was a description of clinical practice in the online and offline learning process during the covid-19 pandemic.  Keywords: Nursing profession student, covid-19 pandemic, perception